Adalimumab for non-infectious uveitis: is it cost-effective?. Issue 11 (6th February 2019) - Bermejo, Inigo; Squires, Hazel; Poku, Edith N; Cooper, Katy; Stevens, John W; Hamilton, Jean; Wong, Ruth; Pearce, Ian; Quhill, Fahd Mohammed; Denniston, Alastair K
Abstract : Background/Aims: Uveitis is inflammation inside the eye. Our objective was to assess the cost-effectiveness of adalimumab compared with current practice (immunosuppressants and systemic corticosteroids) in patients with non-infectious intermediate, posterior or panuveitis and to identify areas for future research. Methods: A Markov model was built to estimate costs and benefits of the interventions. Systematic reviews were performed to identify the available relevant clinical and cost-effectiveness evidence. Data collected in two key randomised controlled trials (VISUAL I and VISUAL II) were used to estimate the interventions' effectiveness compared with the trials' comparator arms (placebo plus limited current practice (LCP)). The analysis was performed from the National Health Service and Personal Social Services perspective. Costs were calculated based on standard UK sources. Results: The estimated incremental cost-effectiveness ratios (ICERs) of adalimumab versus LCP for the base case are £92 600 and £318 075 per quality-adjusted life year (QALY) gained for active and inactive uveitis, respectively. In sensitivity analyses, the ICER varied from £15 579 to £120 653 and £35 642 to £800 775 per QALY for active and inactive uveitis. Conclusion: The estimated ICERs of adalimumab versus LCP are above generally accepted thresholds for cost-effectiveness in the UK. Adalimumab may be more cost-effective in patients with active uveitis at greater risk of blindness. However, there is an unmet need for additional primary data to provide more reliable estimates in several important areas, including effectiveness of adalimumab versus current practice (instead of LCP), incidence of long-term blindness, adalimumab effectiveness in avoiding blindness, and rates and time to remission while on adalimumab.